Sphincter ileostomy - Palma, Eduardo C; González Vales, Horacio; Arias, José (Cirugía del Uruguay, 1972)
The authors describe a new type of ileostomy whe rein a complete ileon shunt ( is performed), while preserving the ileocaecal sphyncter. The details of the technique are described; case material includes 21 patients in whom it was a applied with good results.